Profiling of mineral contents of typical Malaysian muslim foods - Salau, Rasaq Bolakale (2015)
Mineral malnutrition is said to account for )) per cent of the global burden of disease. It is a disease condition in which the amount or concentration of one or more mineral elements known to be essential to human health is found to be low and detrimental to health. Mineral deficiency diseases (MDD) are worth looking into as they could be very drastic, sometimes leading to death or permanent disabilities. The current approaches in tackling the problem of micronutrient malnutrition are based on four options: fortification, supplementation, education and control. This study offers the need to approach the solution to the mineral malnutrition by sourcing the micronutrients from a natural and less cumbersome source like the commonly eaten foods which are accessible, cheaper, needs no expertise and above all, meet the conditions of green health concept. The mineral load of five essential major elements (Ca, Mg, P, K and Na), and nine trace elements (Cr, Co, Cu, Fe, Mn, Mo, Ni, Se and Zn) and three toxic trace elements (As, Cd, and Pb) were quantified in 4) types of Malaysian food dishes samples. The samples were oven dried, homogenised and wet ashed with nitric acid and hydrogen peroxide. The elements were determined using flame photometry, flame atomic absorption spectrometry and inductively coupled plasma mass spectrometry. All of the studied elements were present in the samples. They have good food quality ratios of Ca:P (0.1-2.5) and K:Na (0.9-2.9). When compared with the dietary allowance benchmarks, minimum 40% to maximum ) 80% of values as in K and Se can be met by the foods. Some of the studied foods have self-sufficient and self-supplementing tendency to be relevant in the maintenance of health and management of MDD. The foods are also within safe level. The essential elements were 0.5-63.0% of Upper Tolerable Limit (UL), while, the trace elements were 0.2-77.3% of Provisional Tolerable Daily Intake (PTD1). The score/loading biplot of the Principal Component Analysis (PCA) facilitated the discovery of foods which are mineral rich as well as those prone to toxic elements toxicity. The Hierarchical Cluster Analysis (HCA) dendrogram identified close substitute foods which facilitate wider food choices to the consumers. Finally, a simple food informatics software (MDD-FC) was developed to provide information about MDD, implicated mineral elements as well as the relevant Malaysian food dishes. The software was adjudged simple, user friendly and effective by over 80% end user respondents. In the future, the research could be extended as national project covering more foods and wider geographical regions. Further study on mineral elements bioavabilty in food intakes is also crucial.